The spacetime war - Johnson, Les (Charles Les) (Baen Publishing Enterprises, 2022)
"Humanity has finally made it to the stars. Colony worlds thrive and there is general peace among the settled systems. Until now. Matte black ships of an advanced design appear in colonial systems. Their drives and weapons are not extremely advanced beyond their Terran counterparts - just superior enough to be utterly devastating. Colonies and their populations are obliterated. Once settled worlds are rendered radioactive wastelands. Earth herself lies defenseless before the marauding enemy. DEFEND THE SKIES OF EARTH Standing against the invasion are two of humanity's finest starship captains, Winslow Price of the British Space Navy and Anika Ahuja of the Indian Space Forces. Compatriots. Fierce competitors. Former lovers. Now they are on a quest that will plumb the scientific wells of existence itself, where the primordial knot of spacetime may be unraveling. Price and Ahuja are sworn to do whatever it takes to defend Earth and humanity from ultimate obliteration by an enemy that will not even speak its name. Even if it pushes each to the brink of life and death in battle. Even if it leads each beyond space and time--and to the edge of ultimate possibility!"--